Control of the mechanical and optical properties of SiNx-based films for optical and strain engineering applications - AHAMMOU, Brahim (My University, 2023)
Due to their attractive properties, silicon nitride (SiNx) based films have been recognized as essential dielectric films in the microelectronic and optoelectronic industries. In this PhD thesis, we describe how we can control the refractive index and the mechanical properties of SiNx and silicon oxynitride (SiOyNx) films by tuning the deposition process parameters. We use two different plasma-enhanced chemical vapor deposition reactors: a standard capacitively coupled reactor with radiofrequency excitation and an electron cyclotron resonance reactor with microwave excitation. We discuss the fabrication and characterization of multilayer structures as an optical application of our thin films. We focus on characterizing and understanding these thin films’ optical properties through spectroscopic ellipsometry. We also study their mechanical properties experimentally using the wafer curvature measurement technique, microstructure fabrication, and nanoindentation measurements. Finally, we show accurate measurements of the strain distribution induced within GaAs wafers when such thin films are structured in the shape of elongated stripes of variable width, using standard optical lithography and plasma etching. For this, we map the anisotropic deformation, measuring the degree of polarization of the spectrally integrated photoluminescence (PL) generated within GaAs by excitation with a red laser. PL from bulk cubic semiconductors such as GaAs is unpolarized, whereas anisotropic strain produces some degree of polarization. These maps were measured either from the semiconductor surface or from cleaved cross-sections. They provide a detailed and complete image of the crystal deformation in the vicinity of the structured stressor film. Then, we performed some finite element simulations to reproduce the experimental maps. We believe our simulation scheme is helpful for designing the photonic components, e.g., to predict the local changes in the refractive index due to the photoelastic effect.
Keywords: Silicon Nitride; Plasma Deposition; Optical properties; Mechanical properties; Strain Engineering; Degree Of Polarization